Gestión de promoción empresarial y la formalización de emprendimientos en el distrito de San Juan 2024 - Ramirez Mendoza, Ruth Esther (2025)
This final report investigated the connection between business promotion management and new business formalization in the San Juan district for the year 2024. A descriptive-correlational study was conducted without an experimental approach. A survey of 292 merchants was conducted to collect data. The findings show that both business promotion management and business formalization are considered adequate, with 25% evaluating them positively. A moderate and positive relationship was identified between the various variables, with a Spearman coefficient of 0.727 and a significance level of 0.000. It will also be observed that technical support had a moderate influence, with a coefficient of 0.644, market access with 0.586, and access to technological services with 0.541, all with a significance level of 0.000. Finally, access to financing showed a coefficient of 0.639, equally significant at 0.000.